Comparative analysis of experimental forms of hypo- and hyperthyroid conditions - Sogomonyan , Ye.A.; Chelpanova , I.V.; Pankevych , L.V.; Ambarova , N.A. (Морфологія / Morphologia / Morfologìâ, 2025)
The relevance. Modeling of hypo- and hyperthyroidism in laboratory animals is widely used in modern experimental biology and medicine to study the pathogenetic mechanisms of the development of thyroid gland diseases, the problems of its treatment, as well as the study of the impact of thyroid hormone imbalance on various organs and systems of the body. The most popular method of creating a model of experimental hypothyroidism is the entry of chemicals capable of blocking the function of the thyroid gland into the body of laboratory animals. The most widely used pharmacopoeial thyrostatic is mercazolil, which is used both in clinic for the treatment of thyroid gland diseases which accompanied by hyperthyroidism, as well as in practical experimental studies. Modeling of hyperthyroidism is carried out by entry thyroid hormone preparations into the body of experimental animals. The aim of the work was to determine the optimal doses of drugs, which are necessary to achieve stable hyperthyroid or hypothyroid states, as well as its correction in the experiment. Methods. The experiment was carried out on 65 sexually mature female white rats Wistar line, weighing 200-250 g. All animals were divided into 5 groups: control, hypo- and hyperthyroidism (15 animals in each group), as well as 2 groups with correction of hypothyroidism (10 animals in each group, Table 2.1). The hypothyroid state was modeled with Mercazolil (Zdorovya, Kharkiv) in a daily dose of 10 mg/kg; hyperthyroidism was induced by L-thyroxine (Farmak, Kyiv) in a daily dose of 100 μg/kg body weight of animals. In all experimental groups, mercazolil and thyroxine, in the powder form, were daily added to the food for two weeks, after which the animals were euthanized by an overdose of diethyl ether. The structure of thyroid glands was studied on histological slides stained with hematoxylin and eosin by the traditional method. Results. During the analysis of the micromorphology of the thyroid glands of animals treated with mercazolil, the presence of a goitrogenic reaction was established, which served as evidence of the hypothyroid state induced in this group of animals. A study of the thyroid glands of rats who received thyroxine together with mercazolil at a dose of 1.6 μg/kg of weight (the first correction group) showed that their morphology, both macro- and microscopic, didn`t differ from the group that received only mercazolil, i.e. goitrogenic reaction was present. This indicates an insufficient dose of thyroxine When using a replacement dose of thyroxine of 30 μg/kg of body weight (the second group of correction), the goitrogenic reaction did not develop - the structure of the thyroid glands corresponded to the norm. Thus, it was this dose of thyroxine that compensated for the antithyroid effect of mercazolil. When studying the structure of the thyroid glands of rats treated with thyroxine at a dose of 100 μg/kg, we found signs of their atrophic state. Thus, the macro- and micromorphology of the thyroid glands of rats in this group indicated that the used dose of thyroxine was sufficient to simulate persistent hyperthyroidism.